2013
DOI: 10.3233/nre-130961
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical muscle stimulation and active-assisted cycling improves active range of motion in individuals with Parkinson's disease

Abstract: BACKGROUND: Parkinson's disease (PD) is a neurological disorder which often results in joint rigidity, bradykinesia and decreased range of motion (ROM). Segmental biomechanical muscle stimulation (BMS) can increase ROM in healthy young adults. However, acute effects on ROM in PD have not been examined. OBJECTIVE: To examine whether BMS and active-assisted cycling (AAC) of the legs results in acute changes in ROM in PD. METHODS: Seventeen individuals with PD completed four sessions. Subjects first came to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Our studies, and those of several others, have presented strong evidence that certain exercise interventions promote changes in neural drive in PD ( 3 9 ). Although the exact mechanisms are still unknown, it has been suggested that increases in sensory input or feedback resulting from these interventions may play a role in this motor improvement.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our studies, and those of several others, have presented strong evidence that certain exercise interventions promote changes in neural drive in PD ( 3 9 ). Although the exact mechanisms are still unknown, it has been suggested that increases in sensory input or feedback resulting from these interventions may play a role in this motor improvement.…”
Section: Introductionsupporting
confidence: 70%
“…Animal model studies have shown that high-intensity exercise can promote neural plasticity and neuroprotection against dopaminergic cell loss ( 16 ). Several reports in humans have shown that high-intensity treadmill training ( 17 , 18 ) and high-cadence cycling ( 3 , 6 , 9 , 19 , 20 ) promote functional improvement in PD but there are still several unanswered questions: (1) How does motor function change immediately after high-intensity exercise, (2) What features of exercise (speed, intensity) optimize motor function, and (3) What are potential mechanisms of function improvements after high-intensity exercise?…”
Section: Introductionmentioning
confidence: 99%
“…; Corbett et al . ). However, the mediating mechanisms, including neurotrophic factor hypotheses (Audiffren & André ), remain to be empirically tested in persons with DS undergoing ACT.…”
Section: Discussionmentioning
confidence: 97%
“…It has been proposed that faster movement rates, such as fast cycling cadences, may lead to greater arousal, cortical excitability and cortical neuroplasticity than slower movement rates, not because of greater cardiovascular stress but because of increased afferent stimulation of the corticospinal tract (Schall et al 2003;Wagner et al 2006;Alberts et al 2011;Corbett et al 2013). However, the mediating mechanisms, including neurotrophic factor hypotheses (Audiffren & André 2015), remain to be empirically tested in persons with DS undergoing ACT.…”
Section: Causal Mechanism and Future Researchmentioning
confidence: 99%
“…The FAB also collects foot sole pressure using weight-bearing insoles. This novel device was previously used to evaluate whole body mobility in Parkinson’s disease ( Rahimi et al, 2014 ; Rahimi et al, 2011 ), and velocity and range of motion in cyclists ( Corbett, Peer & Ridgel, 2013 ).…”
Section: Methodsmentioning
confidence: 99%